Leveraging Lesson Study to Develop Technological Pedagogical Content Knowledge in Pre-Service Teacher Education - Endang Darsih; Agie Hanggara; Rizka Andhika Putra (Universitas Pendidikan Ganesha, 2025)
The Pre-Service Teacher Professional Education Program is designed as a strategic initiative to prepare prospective teachers to become competent and professional educators. However, in practice, it continues to face challenges, particularly in integrating technology, pedagogy, and content in a coherent and consistent manner during teaching practicum. This study aims to analyze the implementation of Lesson Study and examine its contribution to the development of Technological Pedagogical Content Knowledge (TPACK) among pre-service teachers. The research employed a qualitative case study approach involving pre-service teachers and supervising lecturers as participants. Data were collected through classroom observations, in-depth interviews, and document analysis of lesson plans and teaching reflections. Data analysis was conducted using thematic analysis through coding, categorization, and interpretation. The findings indicate that Lesson Study establishes a collaborative framework that promotes joint planning, reflective dialogue, and continuous instructional improvement. The enhancement of TPACK was reflected in the shift from basic technology use toward more integrated alignment between pedagogical strategies and subject content. Overall, Lesson Study proved effective in strengthening pre-service teachers’ TPACK competencies. The implications suggest that integrating Lesson Study into professional education programs can serve as a systematic strategy to enhance instructional quality, foster a culture of professional reflection, and prepare adaptive teachers who are responsive to the evolving demands of 21st-century education.